Effects of a prostaglandin F2alpha derivative glaucoma drug on EGF expression and E-cadherin expression in a corneal epithelial cell line. (2nd April 2020) - Takada, Yukihisa; Yamanaka, Osamu; Okada, Yuka; Sumioka, Takayoshi; Reinach, Peter S.; Saika, Shizuya
Abstract: Purpose: We examined the effects of travoprost on cell proliferation-related signals and E-cadherin expression in vitro and in situ in order to obtain evidence to support the hypothesis that topical travoprost impairs the integrity of the corneal epithelium. Methods: A human corneal epithelial cell culture was treated with travoprost (0.4 mg/ml) and/or PD168393 (an EGF receptor inhibitor, 10 μM). The culture was then processed for cell proliferation, an mRNA expression analysis of epidermal growth factor (EGF) and E-cadherin, and protein expression analysis of E-cadherin by immunocytochemistry and Western blotting. The eyes of C57/BL6 mice were incubated in serum-free medium plus travoprost (0.4 mg/ml) and/or PD168393 (10 μM). After being cultured for 24 h, the expression patterns of phospho-EGFR, phospho-ERK, E-cadherin, and Ki67 were immunohistochemically examined in paraffin sections. Results: The addition of travoprost up-regulated EGF mRNA expression and cell proliferation in the corneal epithelial cell culture, and this was cancelled by the addition of PD168393. This FP agonist also decreased E-cadherin expression levels in the cell–cell contact zone, and this was cancelled by the addition of PD168393. In the organ culture, the addition of travoprost to the medium up-regulated the expression of phospho-EGFR and phospho-ERK as well as cell proliferation, and down-regulated the expression of E-cadherin in the corneal epithelium, particularly in basal cells, whereas PD168393 reversed these effects. Conclusions: Travoprost activates epithelial cell proliferation by up-regulating an EGF-related signal in association with the suppression of E-cadherin localization in the cell–cell contact zone. Modulation of the EGF signal may be a strategy to minimize the negative impact of this mitogen on reformation of corneal barrier function during epithelial renewal.